Comparison of insulin requirements across gestation in women with hyperglycemia in pregnancy: A prospective cohort study - Rao, Chong; Ping, Fan (Frontiers in Endocrinology, 2022)
Objectives: To explore the daily insulin dose, the percentage change in preprandial and basal insulin dosage of women with different types of hyperglycemia in pregnancy (HIP) during the whole gestation and postpartum period. Methods: A total of 121 HIP subjects requiring insulin therapy were enrolled from a prospective cohort consisted of 436 pregnant women with hyperglycemia. The subjects were divided into three groups: Group 1 (T1DM and MODY), Group 2 (T2DM) and Group 3 (GDM). The primary study measurements included daily dose and percentage of different types of exogenous insulin requirements across gestation in different groups. Results: Insulin total daily dosage of Group 1 was highest among three groups and increased significantly from first to second/third trimester. Percentage of preprandial insulin increased from 53.8% (46.7, 60.0) and 54.5% (42.3, 62.9) in first trimester to 63.6% (54.9, 75.0) and 67.2% (51.8, 73.7) in second/third trimester in Group1 and Group2. All T1DM and 18.6% T2DM subjects still required insulin administration after delivery, with a 26.9% (19.0, 46.0) and 36.7% (26.9, 52.6) decrease in total insulin dose respectively, while GDM and MODY weaned off insulin completely. Conclusion: The insulin requirements for pregnancy complicated with T1DM and MODY were higher than those for T2DM and GDM. In the subjects with PGDM, insulin requirement, as well as percentage of preprandial insulin increased gradually from early to mid- and late-pregnancy.